2019
DOI: 10.3390/su11164309
|View full text |Cite
|
Sign up to set email alerts
|

How Can Teachers Be Encouraged to Commit to Sustainability? Evaluation of a Teacher-Training Experience in Spain

Abstract: The main objective of this study was to design and evaluate an experience for future teachers focused on the participatory search for sustainability through role play so that outcomes related to improving the way they see the world and their commitment to mitigate climate change could be analysed. The study was carried out with a socio-critical focus, using a qualitative approach. To this effect, semi-open interviews were conducted, and their results were codified and studied using content analysis. The outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 45 publications
3
14
0
1
Order By: Relevance
“…In this sense, Nisiforou and Charalambides [9] suggested that awareness of these problems should be focused on the links between production and consumption, individual habits and the conservation of SES. Therefore, it is Sustainability 2019, 11, 5748 4 of 18 necessary to deepen our knowledge of the pressures exerted by our lifestyle and explore how different educational instruction could improve the understanding of how daily activities are essential to the achievement of sustainability [37][38][39][40].…”
Section: Pressures On Socio-ecological Systems Because Of Certain Actmentioning
confidence: 99%
“…In this sense, Nisiforou and Charalambides [9] suggested that awareness of these problems should be focused on the links between production and consumption, individual habits and the conservation of SES. Therefore, it is Sustainability 2019, 11, 5748 4 of 18 necessary to deepen our knowledge of the pressures exerted by our lifestyle and explore how different educational instruction could improve the understanding of how daily activities are essential to the achievement of sustainability [37][38][39][40].…”
Section: Pressures On Socio-ecological Systems Because Of Certain Actmentioning
confidence: 99%
“…First, the total influence-relation matrix Q can be divided into two matrices: the attribute level Q C and the dimension level Q D . Second, each row within a dimension in the total influence relation matrix Q C uses Equations 7 Equation 7, in which Q ρ11 C is an example to demonstrate the basic concept of normalizing, as shown in Equations (8) and (9).…”
Section: Danp Methodsmentioning
confidence: 99%
“…Teachers play a fundamental role in the reforms [3,8]. While higher education institutions are carrying out reforms in response to the goal of sustainable development, sustainability-based teaching activities pose new challenges to teachers at universities.…”
Section: Introductionmentioning
confidence: 99%
“…Educating future teachers based on activism and critical pedagogy is essential, as it is one of the measures which most influences their students' results [8]. Initial teacher training must therefore address sustainability skills [9,10], through critical, ethical [11,12], conscious [11,13], interdisciplinary and social interaction practices [14,15,13,8.12].…”
Section: 1university Education In Sustainabilitymentioning
confidence: 99%